2022
DOI: 10.47836/ifrj.29.1.05
|View full text |Cite
|
Sign up to set email alerts
|

Aflatoxin B1 contamination of wheat flour, coffee, and pistachios consumed in Northern Palestine

Abstract: The objective of the present work was to investigate the levels of aflatoxin B1 (AFB1) in some commonly consumed food items (wheat flour, roasted coffee beans, and pistachios) at the markets of Palestine. The samples were collected from the cities in the Northern West Bank (Nablus, Tulkarm, and Jenin). The pistachio and coffee samples were collected from the main toasters in these cities, while the flour samples were collected from the major bakeries in these cities. A total of 90 samples were collected, 30 fr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(2 citation statements)
references
References 26 publications
0
2
0
Order By: Relevance
“…Studies have revealed that AFB 1 is present in 64% of USA's chilli samples and 93% of those from Nigeria, with the highest concentrations being 94.9 and 156 g/kg, respectively (Singh & Cotty, 2017). A recent study by Ahmad et al (2022) (Salami Oluwafemi et al, 2019). In addition to the potential toxicity on the affected animals, the introduction of mycotoxin contamination into human food chains through animal-derived products (carryover effects) including meat, milk, and eggs is a significant issue.…”
Section: Aflatoxin Occurrence In Other Foodstuffsmentioning
confidence: 97%
See 1 more Smart Citation
“…Studies have revealed that AFB 1 is present in 64% of USA's chilli samples and 93% of those from Nigeria, with the highest concentrations being 94.9 and 156 g/kg, respectively (Singh & Cotty, 2017). A recent study by Ahmad et al (2022) (Salami Oluwafemi et al, 2019). In addition to the potential toxicity on the affected animals, the introduction of mycotoxin contamination into human food chains through animal-derived products (carryover effects) including meat, milk, and eggs is a significant issue.…”
Section: Aflatoxin Occurrence In Other Foodstuffsmentioning
confidence: 97%
“…A recent study by Ahmad et al. (2022) in Palestine reported the occurrence of AFB 1 in the roasted coffee beans samples ranging between 12 and 49 μg/kg. Beer is the world's most consumed alcoholic beverage.…”
Section: Prevalence Of Aflatoxinsmentioning
confidence: 97%